Piauí state/region (Brazil) semi-arid: expansion and transformation of cashew cultivation in the territory - Alencar, Paulo Gustavo de (2021)
This article aims to analyze some factors that have contributed to the territorial transformations in the semi-arid climate region of the state of Piauí, Brazil, due to the farming expansion of cashew (Anacardium occidentale L.) plantation in the municipality of Pio IX. The present research was based on literature review, interviews, field observations, and satellite image analysis. A territorial development approach has been used to implement development plans for the semi-arid Piauí. Struggles, agrarian conflicts and negotiations has contributed to the creation of rural settlement projects within a region traditionally inclined to cashew production; settlements creation also benefited from the decline in cashew agribusiness. Family farming cashew assumed a leading role in the restructuring of the cashew production sector that took place within this territory, this new order was also favored by the new social and political organizations created by landless workers in order to implement the agrarian reform. Government actions seem to disregard the level of organization exhibited by the cashew productive sector, and besides of being indifferent to related environmental issues. Various development plans has showed some solutions, however, these are not very effective in triggering actions aimed at territorial development.